(untitled) (Journal of Asian Development Studies, 2026)
In this study, the authors analyse the effects of smart shopping perception, salesperson assistance, and socialisation on webrooming behaviour, with financial risk as a moderating factor. PLS-SEM is used to analyse the data and shows that these variables have a significant effect on webrooming behaviour. Physical stores can provide in-store expert advice and foster a positive atmosphere for customers to interact with one another, motivating them to visit physical stores at the time of purchase. Furthermore,customers with a higher financial risk perception are more likely to exhibit webrooming than those with a lower one. Online companies can minimise the financial risk associated with online purchases, retain customers in a single channel –online –and prevent them from switching at the time of purchase.